2020
DOI: 10.1128/jcm.00512-20
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of COVID-19: Current Issues and Challenges

Abstract: 19The COVID-19 outbreak has had a major impact on clinical microbiology laboratories in the past 20 several months. This commentary covers current issues and challenges for the laboratory 21 diagnosis of infections caused by SARS-CoV-2. In the pre-analytical stage, collecting the proper 22 respiratory tract specimen at the right time from the right anatomic site is essential for a 23 prompt and accurate molecular diagnosis of COVID-19. Appropriate measures are required to 24 keep laboratory staff safe while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
1,280
0
56

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,194 publications
(1,345 citation statements)
references
References 68 publications
9
1,280
0
56
Order By: Relevance
“…To slow the spread of the pandemic, screening is the key (5). This allows to isolate positive patients and stop the transmission.…”
Section: Introductionmentioning
confidence: 99%
“…To slow the spread of the pandemic, screening is the key (5). This allows to isolate positive patients and stop the transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The main rationale behind the recent advances in developing diagnostics for COVID-19 is achieving fast and cheap initial detection and confirmation of SARS-CoV-2 infection in different biological samples, including fecal samples, nasopharyngeal or oropharyngeal swabs, and environmental samples. Presently, the clinical testing relies mostly on reverse-transcription quantitative polymerase chain-reaction (RT-PCR) (3,4) in many countries, including developing countries. The viral genome sequencing and even electron microscopy have reportedly been used as confirmatory tests following PCR tests (4).…”
Section: Initial Diagnosis Of Covid-19mentioning
confidence: 99%
“…The authors designed an algorithm to assess patients, presented in Fig.1. This is in contrast to the previous review, "Advice on standardized diagnosis and treatment for spinal diseases during the coronavirus disease 2019 pandemic, " which suggested that chest computed tomography and SARS-CoV-2 nucleic acid test should be performed three days before surgery [3,6]. Patients with confirmed COVID-19 should be transferred to the isolation ward for further treatment.…”
Section: Management Principlesmentioning
confidence: 76%